Application of oil palm and cacao waste biochar to improve the chemical properties of an Ultisol of Langsa, Aceh - Saputra, Iwan; Prijono, Sugeng; Soemarno, Soemarno; Suntari, Retno (Brawijaya University, 2024)
Ultisols, including those of Langsa, Aceh, are known to have low fertility due to low pH, low available nutrients, low base saturation, high pH and exchangeable Al, and low cation exchange capacity. These problems can be alleviated by applying organic amendments to the soil. One of the soil amendments is biochar. This study aimed to elucidate the potential of oil palm and cacao waste biochar for improving the chemical properties of an Ultisol of Langsa, Aceh. Biochars generated from oil palm kernel shell (PKS), oil palm empty fruit bunch (PEFB), and cacao pod husk (CPH) were applied to the soil and incubated in the laboratory for 16 weeks. At 4, 8, 12, and 16 weeks after incubation, the changes in soil chemical properties were measured. The results showed that applying different types of biochar significantly improved the chemical properties of the Ultisol of Langsa. Specifically, PEFB biochar caused significant increases in soil pH (H2O and KCl), total phosphorus, available phosphorus, organic C, and cation exchange capacity. These increases became more pronounced with longer incubation times. In addition, using PEFB biochar resulted in the lowest levels of exchangeable Al and Fe in the soil. These levels decreased further with longer incubation times. In general, PEFB biochar produced at a pyrolysis temperature of 450oC for 4 hours is the most effective biochar for improving the chemical properties of the Ultisol of Langsa.